2017
DOI: 10.1371/journal.pone.0189884
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine for knee osteoarthritis: An overview of systematic review

Abstract: BackgroundTraditional Chinese medicine (TCM) has been accepted as a complementary therapy for knee osteoarthritis. However, the efficacy and safety of the intervention were still conflicting and uncertain. Meanwhile, the quality of methodology and evidence in the field was unknown.ObjectiveTo summarize the characteristics and critically evaluate the quality of methodology, as well as the evidence of systematic reviews (SRs) on TCM for knee osteoarthritis.MethodsFive electronic databases were searched from ince… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 35 publications
0
52
0
6
Order By: Relevance
“…Alternative medicine is popular among Asian older adults (56) as it is believed to be harmless [56,57]. The effectiveness of traditional remedies for knee pain, however, remains controversial [58][59][60][61][62]. The reluctance to accept painkillers appeared to lead to activity avoidance and functional limitations, which are the primary concerns of our older persons with KOA as well as being worried about not being able to observe religious rituals involving kneeing or sitting cross-legged.…”
Section: Plos Onementioning
confidence: 99%
“…Alternative medicine is popular among Asian older adults (56) as it is believed to be harmless [56,57]. The effectiveness of traditional remedies for knee pain, however, remains controversial [58][59][60][61][62]. The reluctance to accept painkillers appeared to lead to activity avoidance and functional limitations, which are the primary concerns of our older persons with KOA as well as being worried about not being able to observe religious rituals involving kneeing or sitting cross-legged.…”
Section: Plos Onementioning
confidence: 99%
“…Therefore, inhibiting chondrocyte apoptosis while promoting the maintenance of healthy chondrocytes represents a potential strategy for preventing cartilage degeneration (37,38). As TCMs are increasingly being used to treat OA (39), scientists have suggested that certain TCMs, particularly those used in combination formulas, may produce therapeutic effects in a synergistic manner. For example, XuanHuSuo powder (XHSP), a conventional herbal formulation developed in China, has been extensively used in OA treatment (40).…”
Section: Discussionmentioning
confidence: 99%
“…OA is one of the most common types of chronic arthritis and seriously affects the quality of life in the elderly population ( 1 3 ). Major pathological features of OA include a series of biological and/or morphological changes, such as the degeneration of articular cartilage, hyperosteogeny and/or sclerosis ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of OA is associated with many parameters, including genetic and immune factors; however, the exact pathogenesis remains unclear ( 3 ). The roles of various miRNAs in OA chondrocytes have been widely studied and have provided a novel research direction, which has helped to elucidate the pathogenesis of OA ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation